Preformulation and Long-Term Stability Studies of an Optimized Palatable Praziquantel Ethanol-Free Solution for Pediatric Delivery - Bedogni, Giselle Rocio (2023)
To date, the treatment for cysticercosis and neurocysticercosis consists of a single oral intake of praziquantel (5–10 mg/kg), which since it is only available as tablets, hinders its administration to pediatric patients. Praziquantel is a poorly water-soluble drug which represents a challenge for its formulation in solution, particularly for the pediatric population. Thus, this study aimed to develop a palatable solution for praziquantel using pharmaceutical-accepted co-solvent systems. A design of experiments approach was applied to identify the optimal conditions for achieving a suitable amount of praziquantel in solution using co-solvent mixtures. Thus, praziquantel solubility increased from 0.38 up to 43.50 mg/mL in the optimized system. A taste masking assay in healthy human volunteers confirmed a successful reduction of drug bitterness after the addition of selected flavors and a sweetener. Stability studies were also conducted at different temperatures (4, 25, and 40 °C) for 12 months Even though the presence of the three known impurities of praziquantel was observed, their amounts never exceeded the acceptance criteria of the USP. Thus, this novel approach should be considered a valuable alternative for further preclinical studies considering the high prevalence of this infection worldwide.